Assessment of accident rates at level crossings in La Habana, Cuba - Hernández Menéndez, Oisy (2025)
The present paper constitutes a deeply of a previous investigation carried out in Cuba in the year 2007 for the same authors, on the behavior of the accident in the level crossing to national scale, in which Havana was identified as the country of more incidence in these facts, that which will be analyzed detailed. The analysis is centered in the statistical aspect with the collection of information on the accidents of the traffic with the objective of determining the municipalities of bigger concentration of the same ones, the lines where they happen, hours of the day and types of vehicles with those that more collide with the trains, and then, to identify for frequency of accidents, the locations at more dangerous levels in the territory, to which will be determined the risks factors that are impacting in this accident in the following phase of the investigation.